The Effect of The Service Quality Dimension on The Satisfaction of Cu Betang Asi Cooperative Members - Leani; Lelo Sintani; Vivy Kristinae (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and analyze the effect of service quality on the member satisfaction of members of CU Betang AsiCooperative in Central Kalimantan Province. The research method is the quantitative method. Primary and secondary data sources and data collection methods used observation, and distributing questionnaires. The sample consisted of 250 respondents, was selected using non-probability sampling techniques through the purposive sampling method The analytical tool is Smart-PLS Version 3.0, to test relationships in conceptual models. Measurement reliability based on alpha value and reliability value of Cronbach composite. The results : The effect of the dimensions of assurance, emphaty, responsiveness on member satisfaction are positive and significant, but reliability and tangibles on member satisfaction are negative and nonsignificant.